Pengaruh Marketing Mix Terhadap Omset Penjualan Pada CV DNA Inspiration of Art Banjarmasin - Mailiana -; masrifani -; Miftahul Jannah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study was to determine the effect of product, price, promotion and location on sales turnover simultaneously and partially and also to find out which variable was the most dominant influence on sales turnover. The population of this study was all consumers of CV DNA Inspiration of Art Banjarmasin in 2015 until 2018. The sample was determined as many as 100 respondents with sampling technique using the Slovin formula. The data analysis method was carried out in a descriptive analysis with multiple linear regression, t test, F test and R2 (coefficient of determination) using SPSS version 25.0. Based on the results of the significance of the partial effect test results obtained that the independent variables namely the product (X1), price (X2), promotion (X3) and location (X4) have a significant effect on sales turnover (Y). This is evidenced from the calculation of the t test in which the significance value is less than a (0.05). The significance of the joint effect test (simultaneous) shows that there is a significant influence between the product (X1), price (X2), promotion (X3) and location (X4) to sales turnover (Y). This is evidenced from the calculation of the F test in which the F count is 139,849 with an F significance of 0,000 which is smaller than a (0.05). The coefficient of determination (R2) is 0.866. This value indicates that the independent variable (product, price, promotion and location) can explain its effect on sales turnover of 86.6%. While the remaining 13.4% is influenced by other variables outside the model. Based on the regression analysis the most dominant variable affecting sales turnover is the product variable with a coefficient of 0.355. Suggestions from this research companies should be able to maintain or even improve product quality, prices can compete with other printing companies and provide discounts for agents or distributors by purchasing large quantities, companies should aggressively carry out promotions, this is due to the increasing number of similar companies by conducting promotions the good the c onsumer will increasingly use printing services and for the location is strategic and easy to reach, but needs to be done in terms of convenience for consumers.